Sequence and overexpression of the menD gene from Escherichia coli. - Popp, J L (1989)
The menD gene of Escherichia coli codes for the first enzyme of menaquinone biosynthesis, 2-succinyl-6-hydroxy-2,4-cyclohexadiene-1-carboxylate (SHCHC) synthase. DNA sequence analysis of menD shows an open reading frame encoding a 52-kilodalton protein. Possible promoter and ribosome binding sites are present. Insertion of the menD gene into a tac promoter expression vector leads to nearly a 100-fold increase in the level of SHCHC synthase activity upon induction with isopropyl-beta-D-thiogalactoside (IPTG). Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of [35S]methionine-labeled proteins shows a 61-kilodalton protein produced upon induction of the menD-containing expression vector. This is the first reported sequence analysis of a men gene and the first significant amplification of any of the menaquinone biosynthetic enzymes.